E-Commerce Adoption among Small and Medium Enterprises (SMEs) in Northern State of Malaysia - Sin, Kit Yeng; Osman, A.; Yusuf, Haji Othman; Safizal, M. (MCSER Publishin, 2015)
Electronic commerce (E-commerce) which is a practice of buying, selling, transferring, or exchanging goods, information or service by means of internet has established in 1994 and until now hordes of organizations have exploited the internet to handle the information and fit in e-commerce into their business processes. This study analyses the relationship between organizational context, technological context, and environmental context towards E-commerce adoption among SMEs in Northern state of Malaysia which comprise of Perlis, Kedah, Penang and Northern part of Perak. Above and beyond, this study is conducted based on survey design and descriptive research investigation. Entire numbers of respondents collected through questionnaires are 364 CEOs or managers diversified from different sectors. The research data is analyzed using frequency analysis, reliability analysis, descriptive analysis as well as multiple regression analysis.